2008
DOI: 10.3928/15394492-20080301-05
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Performance, Self-Esteem, and Quality of Life in Substance Addictions Recovery

Abstract: A non-randomized pretest—posttest design was used to evaluate changes in occupational performance, self-esteem, and quality of life among clients completing a substance abuse recovery program that included occupational therapy services addressing life skills. Seventy-five clients participated in intake and discharge assessment (4- to 6-month interval) that used the Occupational Performance History Interview (Version 2.0), the Rosenberg Self-Esteem Scale, and the Quality of Life Rating scale. A limited number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 22 publications
4
17
0
12
Order By: Relevance
“…When combined, the MOHO and the cognitive behavioral therapy (CBT) model are compatible in developing coping skills because self-concept and self-esteem can be seen as part of the volitional subsystem, which affects an individual's willingness to act and is tied to the issues of self-competence, mastery and self-effi cacy (Moyers, 1992;Stoffel, 1993;Kielhofner, 2002). Martin et al (2008) utilized a MOHO approach to study the outcomes of a programme utilizing occupational therapy to develop occupational performance skills in persons undergoing treatment for SUD and found signifi cant improvements and large effect size in occupational competence, occupational identity, self-esteem and quality of life. Each of these areas has an important role in the development and maintenance of recovery and is essential in a peer-supported community.…”
Section: Introductionmentioning
confidence: 99%
“…When combined, the MOHO and the cognitive behavioral therapy (CBT) model are compatible in developing coping skills because self-concept and self-esteem can be seen as part of the volitional subsystem, which affects an individual's willingness to act and is tied to the issues of self-competence, mastery and self-effi cacy (Moyers, 1992;Stoffel, 1993;Kielhofner, 2002). Martin et al (2008) utilized a MOHO approach to study the outcomes of a programme utilizing occupational therapy to develop occupational performance skills in persons undergoing treatment for SUD and found signifi cant improvements and large effect size in occupational competence, occupational identity, self-esteem and quality of life. Each of these areas has an important role in the development and maintenance of recovery and is essential in a peer-supported community.…”
Section: Introductionmentioning
confidence: 99%
“…In a mixed study on body image for women recovering from alcohol abuse, Van Deusen (2000) found that while positive body image did not appear to relate to recovery, occupational patterns were consistent during prolonged recovery. Martin et al (2008) also found some consistency over time in the occupational performance, self esteem, and quality of life for people who attended life skills training from an occupational therapist. Significant improvements and large effect sizes were found for many variables over a 4-6-month period, but there was a decline for some clients at follow-up.…”
Section: Methodsmentioning
confidence: 82%
“…Two studies focused on the experience of parenting while either continuing to use substances (Knis-Matthews 2010) or in recovery (Martin et al 2008). Both used qualitative methods to explore this area, and clearly identified a role for occupational therapy in supporting people in their parenting responsibilities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations